Analytical Homoclinic Solution of a Two-Dimensional Nonlinear System of Differential Equations. (11th December 2013) - Maaita, J. O.; Meletlidou, E.
Abstract : Analytical solution of the homoclinic orbit of a two-dimensional system of differential equations that describes the Hamiltonian part of the slow flow of a three-degree-of-freedom dissipative system of linear coupled oscillators with an essentially nonlinear attachment is described.